2003
DOI: 10.1128/jcm.41.2.671-674.2003
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Reliability of Focus Glycoprotein G-Based Type-Specific Enzyme Immunoassays for Detection of Herpes Simplex Virus Types 1 and 2 in Women

Abstract: Serologic assays that utilize herpes simplex virus (HSV) type-specific glycoproteins G-1 (HSV-1) and G-2 (HSV-2) to discriminate between antibodies against HSV-1 and HSV-2 are sensitive and specific. However, the high rates of seroreversion, defined as the change in an individual's antibody status from positive to negative over time, previously reported in longitudinal evaluations of glycoprotein G type-specific tests suggests that their use in HSV acquisitional studies would be problematic. To further explore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…However, in this study, the selected peptides of gG region were not found to be immunodominant epitopes for the diagnosis of HSE. There are studies supporting these findings which state the limits in reliability of gG based type-specific serologic assays for HSV-1 and HSV-2 due to the high rates of seroreversion, defined as the change in an individual's antibody status from positive to negative over time, suggesting that their use in HSV acquisitional studies would not be useful (Schmid et al, 1999;Cherpes et al, 2003).…”
Section: Discussionmentioning
confidence: 93%
“…However, in this study, the selected peptides of gG region were not found to be immunodominant epitopes for the diagnosis of HSE. There are studies supporting these findings which state the limits in reliability of gG based type-specific serologic assays for HSV-1 and HSV-2 due to the high rates of seroreversion, defined as the change in an individual's antibody status from positive to negative over time, suggesting that their use in HSV acquisitional studies would not be useful (Schmid et al, 1999;Cherpes et al, 2003).…”
Section: Discussionmentioning
confidence: 93%
“…The reported rate for discordant consecutive results for the HerpeSelect ® HSV‐2 is <0.1% [Cherpes et al, ]. Previous data indicated an HSV‐2 prevalence of 51.5% in this clinic population [Burton et al, ].…”
Section: Methodsmentioning
confidence: 91%
“…Alternatively, the patient's immune system could have been incapable of mounting an immune response to HSV gG, or he could have lost this response [Schmid et al, 1999;Cherpes et al, 2003]. Unfortunately, serum samples dating back to 1996 were no longer available; his seroconversion at the time had been demonstrated using the Radim ELISA.…”
Section: Discussionmentioning
confidence: 96%